Efecto del extracto Etanólico de Caesalpinia spinosa tara o tara sobre el crecimiento de Salmonella typhi y Escherichia coli en condiciones de laboratorio - Cholán Pacheco, Karina Elizabeth (2018)
ABSTRACT The objective of the present investigation was to evaluate the effect of the ethanolic extract of Caesalpinia spinosa "tara or taya" on the growth of Salmonella typhi and Escherichia coli under laboratory conditions using a completely randomized block design. The mature pods of C. spinosa "tara" were washed with water and 1% sodium hypochlorite, then placed in the oven for drying at 40 ° C for a period of 48 hours, followed by pulverization in a mill, the obtained sample was prepared the 70% ethanolic extract by placing it in an amber bottle for 10 days with agitation; finally obtained the extract was brought to 40 ° C in the stove for the evaporation of the alcohol. The evaluation of the effect of the ethanolic extract was carried out using the modified Kirby Bauer method, instead of using disks, holes were used made with a sterile steel punch 0.6 mm in diameter. Four holes with a diameter of 7 mm and a depth of 5 mm were made in each plate. In each of the holes, 50 uL of the ethanolic extract of C. spinosa was placed at concentrations of 200 mg / ml; 400 mg / ml and 800 mg / ml respectively; We worked with a positive control (ciprofloxacin drug disk) and a negative control (2% Dimethylsulfoxide), finally the plates were incubated at 37ºC for 24 hours and finally the diameters (mm) of the inhibition halos formed were measured. The results show that the higher concentration of the tatan ethanolic extract, there is greater growth inhibition of both bacteria, S. typhi being the one with the greatest inhibition diameter (29.33 mm) at the concentration of 800mg / ml, while E coli has an inhibition diameter of (24.44 mm) at the concentration of 800 mg / ml. It is concluded that the ethanolic extract of C. spinosa "tara" at different concentrations inhibits the growth of Salmonella typhi and Escherichia coli under laboratory conditions.